MiR-19a and miR-20a and Tissue Factor Expression in Activated Human Peripheral Blood Mononuclear Cells. (30th October 2017) - Balia, Cristina; Giordano, Mirella; Scalise, Valentina; Neri, Tommaso; Fontanini, Gabriella; Basolo, Fulvio; Celi, Alessandro; Pedrinelli, Roberto
Abstract : Background and Aims . To investigate the behaviour of miR-19a and miR-20a, two microRNAs involved in posttranscriptional modulation of TF expression in peripheral blood mononuclear cells (PBMCs) exposed to high glucose (HG) and lipopolysaccharide (LPS), and to evaluate the involvement of angiotensin II in that process. Methods . TF Procoagulant Activity (PCA, one-stage clotting assay), antigen (Ag, ELISA), and miR-19a and miR-20a levels (specific TaqMan® MicroRNA Assays) were evaluated in PBMCs exposed to high glucose (HG, 50 mM), LPS (100 ng/mL), and Olmesartan (OLM, 10 −6  M), an angiotensin II type 1 receptor antagonist. Results . HG increased TF expression and decreased both miRs as compared to control glucose conditions (11.1 mM). In HG-activated PBMCs, LPS stimulated TF expression and downregulated miR-20a, an effect reverted by OLM (10 −6  M); miR-19a expression was unchanged by LPS in both CG and HG conditions. Conclusions . miR-19a and miR-20a are inhibited by inflammatory stimuli active on TF expression and their response differs by the stimulus under investigation; angiotensin II may participate in that mechanism.